Run, Walk, Crawl: Towards Dynamic Link Capacities - Singh, Rachee; Ghobadi, Manya; Foerster, Klaus-Tycho; Filer, Mark; Gill, Phillipa (Proceedings of the 16th ACM Workshop on Hot Topics in Networks, 2017)
Fiber optic cables are the workhorses of today’s Internet services. Operators spend millions of dollars to purchase, lease and maintain their optical backbone, making the efficiency of fiber essential to their business. In this work, we make a case for adapting the capacity of optical links based on their signal-to-noise ratio (SNR). We show two immediate benefits of this by analyzing the SNR of over 2000 links in an optical backbone over a period of 2.5 years. First, the capacity of 80% of IP links can be augmented by 75% or more, leading to an overall capacity gain of 145 Tbps in a large optical backbone in North America. Second, at least 25% of link failures are caused by SNR degradation, not complete loss-of-light, highlighting the opportunity to replace link failures by link flaps wherein the capacity is adjusted according to the new SNR. Given these benefits, we identify the disconnect between current optical and networking infrastructure which hinders the deployment of dynamic capacity links in wide area networks (WANs). To bridge this gap, we propose a graph abstraction that enables existing traffic engineering algorithms to benefit from dynamic link capacities. We evaluate the feasibility of dynamic link capacities using a small testbed and simulate the throughput gains from deploying our approach.